An extra cochlear electro-stimulating device (ECME) using atraumatic external meatal electrodes as a communication aid for the deafened - BOCHENEK, W.; CHORZEMPA, A.; HAZELL, J. W.; KUKWA, A. J.; KICIAK, J. (Archives of Acoustics, 1990)
We describe an auditory prosthesis for totally deafened people which stimulates both cochlear via ear canal electrodes. The device emits a square wave pulse matched to the first formant frequency and transposed below 10 Hz. It acts as an aid to lipreading, creates an awareness of environmental sounds, and reduces the isolation of total deafness. It is a cheap non-surgical alternative to cochlear implantation.